Development of BeO:Na, Yb, Dy ceramics for optically stimulated luminescence dosimetry. (November 2022) - Altunal, V.; Jain, M.; Hayat, S.; Guckan, V.; Yegingil, Z.
Abstract: This paper presents the structural and luminescence characterization of undoped and trivalent lanthanide-doped BeO ceramics synthesized via the co-precipitation synthesis technique. Phase confirmation of the products was achieved by the x-ray diffraction (XRD) method, while the surface and elemental morphology were carried out with scanning electron microscopy (SEM)/energy dispersive spectrum (EDS) analyses. Radioluminescence (RL), Thermoluminescence (TL) and Optically stimulated luminescence (OSL) methods were utilized for the luminescence characterization. Moreover, the relationship between TL and OSL signals was investigated in-depth with three different experiments (TL after OSL, step annealing and thermally-transferred OSL (TT-OSL). The radiation sensitivity of BeO:Na5%, Yb0.2%, Dy0.01% ceramics was found to be high as a peak OSL signal of 1.3 × 10 4 counts/mg for 0.2 Gy beta dose. A wide green emission band between 475 and 625 nm was detected for the first time in the RL emission spectra of doped/undoped BeO ceramics. It has been found that the RL and TL emissions of BeO ceramics have partially similar luminescence mechanisms and the TL traps responsible for the ∼315 °C TL peak are the main source of OSL signals. The Tm -Tstop method, Eac -Tstop graph and deconvolution of TL glow curve have been conjunctionally used to estimate kinetic parameters of TL traps in BeO:Na5%, Yb0.2%, Dy0.01% pellets. The results demonstrate that the TL glow curve has at least five TL peaks at 172 ± 2, 223 ± 2, 316 ± 2, 356 ± 2 and 465 ± 2 °C with estimated activation energies 1.13, 1.16, 1.39, 1.41, and 1.99 eV, respectively. The dosimetric characteristics of BeO:Na5%, Yb0.2%, Dy0.01% pellets have been also performed by reusability, dose-response, and fading experiments, and the results show that the material is promising and encouraging for use in dosimetric applications. Highlights: BeO:Na5%, Yb0.2%, Dy0.01% ceramics were synthesized by the co-precipitation technique. The effect of lanthanide dopants on structural characteristics of BeO ceramics was investigated. TL and RL emissions BeO-based ceramics originate from different luminescence processes. OSL signals were found to be nearly linear between 0.5 and 100 Gy, reusable up to 30 cycles, and low faded. The trap parameters of the material were estimated using Tm -Tstop and CGCD techniques.